Hierarchical procedure for creating local typologies for riparian zone research and management based on biophysical features. (4th March 2018) - Flores-Díaz, Adriana C.; Guevara Hernández, Roger; Mendoza, Manuel E.; Langrave, Rosario; Quevedo, Alexander; Maass, Manuel
Abstract: Riparian systems have been included as a key component in ecosystem management because of their role in buffering the impact of land-use activities on fluvial systems. Riparian knowledge can be enhanced with a typology that reflects the multiple relationships occurring throughout the landscape. We propose a hierarchical procedure based on biophysical aspects for building local to regional typologies for guiding research and management, using the Cuitzmala River Basin as a case study. The variables involved were obtained from geospatial databases, water balances, and topographic profiles. The levels and variables are context (altitude, geoform [mountains/hills/plains], and runoff coefficient), structure (stream order, longitudinal slope, hydroperiod, and segment length), and microstructure (lateral slope, bankfull width, and length-to-width ratio). We consider humidity and functional gradient along the basin to identify groups of streams and fluvial networks. Inside each network, we described structural and microstructural features associated with riparian functions, linking them with management decisions. Therefore, the proposed hierarchical procedure can help in making riparian heterogeneity visible, focusing research and management goals, and allowing the recognition of a spatial dimension of the processes being studied.